Where's the logic in commissioning?: exploring the influence of institutional logics on inter-organisational working in the English National Health - O'Connor, Rebecca (2018)
This thesis explores inter-organisational relationships and behaviours when complex healthcare pathways are planned, designed, procured and implemented in the English National Health Service (NHS) in a process known as commissioning. Commissioning and healthcare provision in the NHS is organised separately and operates as a quasi-market system. Clinical Commissioning Groups (CCGs) commission the majority of local healthcare for their populations and purchase services accordingly from many different types of healthcare provider organisations. Poor integration between different provider organisations has been suggested a contributing factor to the unsustainable demands the NHS is currently facing. New models of provision have been recommended in policy as a commissioning strategy to improve integration and these require collaboration and effective inter-organisational working between organisations.